The Relationship of Smoking Status and Ventilation Extent with The Incident of Tuberculosis - Nisak, Irma Dwi Khoirun; Abidin, Zaenal; Ramadanintyas, Karina Nur (Syntax Corporation Indonesia, 2024)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium Tuberculosis and attacks the organs or tissues of the human body, especially the lungs, which is caused by an imbalance between the environment, agent and host. Factors that can cause the spread of tuberculosis, if treatment is not carried out quickly, will cause an increase in the number of cases of tuberculosis. The aim of this research is to analyze the relationship between family smoking status and ventilation area with the incidence of tuberculosis in the working area of ​​the Banjarejo Community Health Center, Madiun City. In this research, researchers used quantitative research as an approach. The research method used is an analytical survey while the type of research is Case Control. The total population was 35 tuberculosis cases with a sample size of 52 respondents who were divided between the case group and the control group using the Chi-Square test. The results of the study showed that there was a significant relationship between the independent variables of family smoking status (p-value = 0.018), ventilation area (p-value = 0.007) with the incidence of tuberculosis in the working area of ​​the Banjarejo Community Health Center, Madiun City.